Counsellors' Approaches in Handling Online Counseling in The Midst of COVID-19 - Shazli, Akmal Nazihah; Mahalle, Salwa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose of this study is to explore the counsellors' online experiences during the COVID-19 pandemic that hit Brunei in August 2020 where all educators were forced to shift from physical to virtual meetings. Semi-structured interview was conducted with six counsellors from secondary government school in Brunei Darussalam who experienced online counseling during the medium transition period. From the interview, the data was transcribed and categorized the responses in different themes. Using thematic analysis, it was found that e-counseling is possible provided that counsellors are future ready, equipped with necessary skills, knowledgeable and skillful. In addition, experienced counsellors shared information on how to improve online counseling services as well as the challenges they encountered throughout carrying out the sessions online. This study could be beneficial to add as literature and useful for future researchers to conduct similar research based on this research topic.